The Effect Of Teaching Basics Of English Morphology On EFL Students' Vocabulary Mastery - Mayra Musdalifah; Zaitun Qamariah (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study investigates the impact of introducing the basics of English morphology to English as a Foreign Language (EFL) students. Morphology, the study of word formation and structure, is fundamental to understanding and mastering any language. The research focuses on how foundational knowledge of English morphology influences EFL students' language acquisition and proficiency. By incorporating morphological instruction into the curriculum, students can enhance their vocabulary, improve their reading comprehension, and develop a deeper understanding of grammatical structures. The study involved a group of EFL students who received systematic instruction in morphology, including the identification and usage of roots, prefixes, and suffixes. Pre- and post-tests were administered to measure the student's progress. The results indicated a significant improvement in the student's linguistic skills, particularly their ability to decode and construct words and overall language comprehension. The findings suggest that integrating morphology into EFL teaching strategies can provide substantial benefits, facilitating more effective language learning and boosting students' confidence in English. This research underscores the importance of morphological awareness in EFL education and offers practical implications for educators aiming to enhance their teaching methods to support student success in acquiring English.